Latin American Television: A Global View - Sinclair, John (Oxford University Press, 1998)
Latin American Television makes English speakers aware of the dimensions, operation, and significance of the globalization of television in the Spanish-speaking world. Second only in scale to the market for English-language programming, the Spanish-language market embraces not just most nations of South and Central America but also Spain, and even the United States--the sixth largest Spanish-speaking country in the world. This intercontinental space is connected physically by satellite communication, and culturally by a common language and heritage which binds it as both a `geolinguistic region' and an `imagined community' which certain media corporations, Latin American and North American, seek to exploit. A similar phenomenon with regard to Brazil and the Portuguese-speaking world is ... Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

New Flows in Global TV - Moran, Albert (Intellect Books, 2009)
New Flows in Global TV provides a pioneering investigation into television distribution worldwide and the global trade in television program formats. Topics include explorations of how shows like Who Wants to Be a Millionaire? and Big Brother are reformatted for audiences in diverse markets such as Argentina, South Africa, the Middle East, and China; the international circulation of Dallas in the 1980s; and Australian and United Kingdom programming exports in the last decade. Moran argues that distribution is the crucial link in a chain that dictates the consumption and purchase of television content. Consequently, New Flows in Global TV will be a key text for scholars of global media, providing comprehensive insight into the cultural, social and economic exchanges underlying media programming.
Keywords: 1-TV; 2-Étude des industries culturelles; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Understanding the Global TV Format - Moran, Albert; Malbon, Justin (Intellect Books, 2006)
This volume presents a series of papers concerned with the interrelations between the postmodern and the present state of art and design education. Spanning a range of thematic concerns, the book reflects upon existing practice and articulates revolutionary prospects potentially viable through a shift in educative thinking.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Playing with Race: The Ethics of Racialized Representations in E-Games - Chan, Dean (Internaitonal Review of Information Ethics, 2005)
Questions about the meanings of racialized representations must be included as part of developing an ethical game design practice. This paper examines the various ways in which race and racial contexts are represented in a selected range of commercially available e-games, namely war, sports and action-adventure games. The analysis focuses on the use of racial slurs and the contingencies of historical re-representation in war games; the limited representation of black masculinity in sports games and the romanticization of ‘ghetto play’ in urban street games; and the pathologization and fetishization of race in ‘crime sim’ action-adventure games such as True Crime: Streets of LA. This paper argues for, firstly, a continuous critical engagement with these dominant representations in all their evolving forms; secondly, the necessary inclusion of reflexive precepts in e-games development contexts; and thirdly, the importance of advocating for more diverse and equitable racialized representations in commercial e-games.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé